Transcriptional regulation of the sucrase gene of Staphylococcus xylosus by the repressor ScrR. - Gering, M (1996)
In Staphylococcus xylosus, scrB is one of two genes necessary for sucrose utilization. It encodes a sucrase that hydrolyzes intracellular sucrose-6-phosphate generated by the uptake of sucrose via the sucrose-specific enzyme II of the phosphotransferase system, the gene product of scrA. ScrB sucrase activity is inducible by the presence of sucrose in the culture medium. Primer extension experiments demonstrated that the observed regulation is achieved at the level of scrB transcription initiation. The protein mediating sucrose-specific regulation of scrB was found to be encoded immediately upstream of the sucrase gene. The nucleotide sequence of the regulatory gene scrR comprises an open reading frame that specifies a protein of 35.8 kDa. This protein exhibits similarity to transcriptional regulators of the GalR-LacI family. Inactivation of the scrR reading frame in the genome of S. xylosus led to the constitutive expression of scrB at a high level, identifying ScrR as a repressor of transcription. Sucrose-specific regulation of scrB was also lost upon deletion of 4 bp of a palindromic sequence (OB) covering positions +6 to +21 downstream of the scrB transcriptional start site. These results suggested a direct interaction of the ScrR repressor and the operator OB. Accordingly, a fusion protein consisting of the maltose-binding protein of Escherichia coli and the ScrR protein was able to interact with an scrB promoter fragment in gel mobility shift experiments but failed to bind an scrB fragment carrying the 4-bp deletion derivative of OB. An scrR promoter fragment, which dose not contain a sequence resembling OB, was not shifted by the fusion protein. This result corroborates scrR primer extension analyses showing that transcription of the repressor gene itself is not regulated. Therefore, the sucrase gene operator OB is the target sequence through which the ScrR protein exerts its negative effect on transcription initiation. In the promoter region of scrA, the gene essential for sucrose transport, two palindromic sequences that are similar to the scrB operator are found. Their presence in scrA suggests that ScrR controls a sucrose-specific regulon in S. xylosus.